Quantitative assessment of growing hair counts, thickness and colour during and after treatments with a low‐fluence, home‐device laser: a randomized controlled trial. (13th December 2014) - Thaysen‐Petersen, D.; Barbet‐Pfeilsticker, M.; Beerwerth, F.; Nash, J.F.; Philipsen, P.A.; Staubach, P.; Haedersdal, M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Available evidence shows hair reduction up to 12 months after low‐fluence light‐based treatments. Previous studies quantified hair reduction by manual hair counts and assessed thickness and colour by patient assessment. What does this study add? Computer‐aided quantification showed stable reduction of growing hair counts, thickness and colour during sustained low‐fluence laser treatment. The reduction was reversible and hairs regrew after treatment cessation. Computer‐aided image analysis is qualified for assessment of growing hair counts, thickness and colour.